Reduction of incidence and relapse or recrudescence cases of malaria in the western region of the Brazilian Amazon - Vieira, Gabriel de Deus; Gim, Karla Nayma Mundt; Zaqueo, Guilherme Mendes; Alves, Thaianne da Cunha; Katsuragawa, Tony Hiroshi; Basano, Sergio de Almeida; Camargo, Luís Marcelo Aranha; Maciel de Sousa, Camila (The Journal of Infection in Developing Countries, 2014)
Introduction: Malaria is one of the major parasitic diseases in the State of Rondônia, located in the western Brazilian Amazon. The basic treatment scheme for this disease is chloroquine and primaquine. This study evaluated the epidemiological profile of malaria in Rondônia between 2008 and 2012. Methodology: The epidemiological data were provided by the Health Surveillance Agency from the State of Rondônia, and socioeconomic indicators were obtained from the Brazilian Institute of Geography and Statistics, Department of Informatics of the Unified Health System, and from the National Institute for Space Research. The analyzed variables included year of diagnosis, gender, age group, main activity performed in the 15 days previous to the diagnosis, parasite species, level of parasitemia, number of relapse/recrudescence cases, and socioeconomic and environmental data for Rondônia. Results: A total of 238,626 cases of malaria were recorded in Rondônia during the study period. Of this total, 65.6% were men and the most prevalent age group was 20–39 years. Plasmodium vivax was the most common parasite (89.8%), followed by Plasmodium falciparum (9.4%). An average of 30.9% of the individuals who were tested presented with relapse/recrudescence malaria. The API value was highest in 2008 and lowest in 2012, corresponding to 42.3 cases and 19.2 cases per 1,000 inhabitants, respectively. Conclusions: A 58% reduction in the number of malaria cases and a 36.2% reduction in the number of relapse/recrudescence malaria cases were observed, due to increases in the economy, improvements in the health system, and reduction of deforestation in this region.